2012
DOI: 10.1007/s10811-012-9805-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the microbial digestion of an industrial seaweed-based residue

Abstract: Commercial preparation of a seaweed extract from the brown alga Ascophyllum nodosum for use as fertiliser and soil improver produces a sludge residue which requires remediation. This residue is rich in nutrients and offers the potential for other value-added products. The residue composition was analysed, a microbial digestion process for the residue was developed, and several factors affecting the digestion process were studied. The residue showed an alkaline pH (8.61±0.39) and 16% (w/w) total solids, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Also, biodegradability of biomass can be affected by several other factors like crystalline structure, the extent of cellulosic polymers, the surface properties of biomass, the amount of lignin content, the presence of hemicellulosic materials and the strength of fibers [44]. Other relevant studies were conducted on factors affecting the microbial digestion of an industrial seaweed-based residue of AN post alginate extraction [45,46]. The residue characterised by these showed an alkaline pH of the substrate prior to digestion and the authors identified that the digestibility was influenced by soluble/insoluble matter and inocula's metabolite inhibition, which are critical features for the digestion of the residues.…”
Section: Effect Of Inoculum Acclimatation On Methane Productionmentioning
confidence: 99%
“…Also, biodegradability of biomass can be affected by several other factors like crystalline structure, the extent of cellulosic polymers, the surface properties of biomass, the amount of lignin content, the presence of hemicellulosic materials and the strength of fibers [44]. Other relevant studies were conducted on factors affecting the microbial digestion of an industrial seaweed-based residue of AN post alginate extraction [45,46]. The residue characterised by these showed an alkaline pH of the substrate prior to digestion and the authors identified that the digestibility was influenced by soluble/insoluble matter and inocula's metabolite inhibition, which are critical features for the digestion of the residues.…”
Section: Effect Of Inoculum Acclimatation On Methane Productionmentioning
confidence: 99%
“…This newly isolated cellulose-degrading bacterium and its cellulase properties from the coffee pulp was novel research that had never been published before. Nevertheless, the cellulose-degrading capacity of Leclercia adecarboxylata has been indicated by other researchers (Nogales et al 2012;Yadav et al 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, kelp residue had been usually added as accessory material in the feed for livestock farming and aquaculture such as for broiler chicken, Litopenaeus vannamei, and so on (Ahmed, Mun, Islam, & Yang, 2014;Martínez & Olvera, 2016;Peng, Chang, Ma, & Li, 2017). With the metabolic activity of microorganisms, the raw material of the feed is converted to small molecules such as peptides, amino acids and reducing sugars, resulting in more nutrient availability (Nogales, Concannon, & Hall, 2012). Therefore, the kelp residues appear to be viable as an effective sea cucumber feedstuff and can supplement the shortage of Sargassum thunbergii in the current sea cucumber feed industry.…”
mentioning
confidence: 99%
“…Fermented feed is obtained by degrading material with appropriate microorganisms. With the metabolic activity of microorganisms, the raw material of the feed is converted to small molecules such as peptides, amino acids and reducing sugars, resulting in more nutrient availability (Nogales, Concannon, & Hall, 2012). The fermented feed has better palatability and is more easily digested and absorbed (Akinola, Onakomaiya, Agunbiade, & Oso, 2015;Alshelmani, Loh, Foo, Sazili, & Lau, 2016).…”
mentioning
confidence: 99%